2012
DOI: 10.1016/j.exer.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Individual versus collective fibroblast spreading and migration: Regulation by matrix composition in 3D culture

Abstract: Extracellular matrix (ECM) supplies both physical and chemical signals to cells and provides a substrate through which fibroblasts migrate during wound repair. To directly assess how ECM composition regulates this process, we used a nested 3D matrix model in which cell-populated collagen buttons were embedded in cell-free collagen or fibrin matrices. Time-lapse microscopy was used to record the dynamic pattern of cell migration into the outer matrices, and 3-D confocal imaging was used to assess cell connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 46 publications
4
49
1
Order By: Relevance
“…We previously demonstrated that cells interacting with collagen matrices develop dendritic processes and move independently, whereas cells interacting with fibrin matrices develop stress fibers and form an interconnected meshwork [24, 25]. In constructs in which cell-seeded compressed collagen matrices are nested within acellular fibrin matrixes, interconnected streams of cells are formed during migration into fibrin (Supplemental Movie 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that cells interacting with collagen matrices develop dendritic processes and move independently, whereas cells interacting with fibrin matrices develop stress fibers and form an interconnected meshwork [24, 25]. In constructs in which cell-seeded compressed collagen matrices are nested within acellular fibrin matrixes, interconnected streams of cells are formed during migration into fibrin (Supplemental Movie 1).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, whereas corneal fibroblasts generally move independently within 3-D collagen matrices, fibrin induces a switch to an interconnected, collective mode of cell spreading and migration which is independent of differences in ECM stiffness [24, 25]. Fibronectin is an adhesive protein secreted by cells that facilitates binding to other ECM proteins [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations